2019
DOI: 10.1080/17512433.2019.1605903
|View full text |Cite
|
Sign up to set email alerts
|

Reported needs of information resources, research tools, connectivity and infrastructure among African Pharmacological Scientists to improve future patient care and health

Abstract: Introduction: The potentials of Africa for growth and economic transformation through science remains challenging because of existing gaps in knowledge and infrastructure. The Africa Pharmacological Science Gateway project and the Medicines Utilization Research in Africa Group seeks to meet the research needs of African pharmacologists. This study aimed at identifying priority needs that might be met by access to information and tools through einfrastructure. Methods: A web-based cross-sectional study among 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…There is a need to define and provide access to essential drug information for optimal care in resource-strained countries [77,78]. With relatively limited funding, many sources of information developed across the globe could become available in resource-strained countries by joint initiatives from learned societies, public funders and private-public partnerships and using already existing available technology platforms.…”
Section: Public Funding Of Open Knowledge Basesmentioning
confidence: 99%
“…There is a need to define and provide access to essential drug information for optimal care in resource-strained countries [77,78]. With relatively limited funding, many sources of information developed across the globe could become available in resource-strained countries by joint initiatives from learned societies, public funders and private-public partnerships and using already existing available technology platforms.…”
Section: Public Funding Of Open Knowledge Basesmentioning
confidence: 99%
“…8 -10 A number of studies have shown that the interaction with PSRs influences the prescribing pattern of physicians, which can lead to irrational prescribing of medicines and higher costs. 2,5,11 -14 However, others have shown that the influence of PSRs on the prescribing pattern of physicians can be minor. 15,16 A concern is that pharmaceutical companies can omit vital information about adverse effects of the medicines they market to make them more attractive to prescribers.…”
Section: Introductionmentioning
confidence: 99%